Syntactic analysis of natural languages based on context-free grammar backbone - Kadlec, Vladimír; Pala, Karel, 1939-2023; Masarykova univerzita. Katedra informačních technologií (2007)
The aim of the thesis is to design algorithms and methods for an effective and robust syntactic analysis of natural languages. The algorithms are language-independent, any language with an appropriate grammar can be modeled. The analysis of sentences by the described system is based on context-free grammar for a given language supplemented by context sensitive structures. The internal representation of derivation trees allows applying contextual constraints, e.g. case agreement fulfillment. The result of the constraint application is still stored in the polynomial structure. The evaluation of semantic actions and contextual constraints helps us to reduce a huge number of derivation trees and we are also able to calculate some new information, which is not contained in the context-free part of the grammar. Also n-best trees (according to a tree rank, e.g. probability) can be selected. This is an important feature for linguistics developing a grammar by hand. We describe a robust extensi.
Vedoucí práce: Karel Pala.
Dizertace (Ph.D.)--Masarykova univerzita, Fakulta informatiky, 2008.
Keywords: mluvnice; neurolingvistické programování; algoritmy (programování); syntax; grammar; neurolinguistic programming; algorithms; syntax; disertace; dissertations